Magneto-hydro dynamic flow and heat transfer of non-newtonian power-law fluid over a non-linear stretching surface with viscous dissipation - Kishan, Naikoti; Kavitha, P. (Zielona Góra: Uniwersytet Zielonogórski)
A fluid flow and heat transfer analysis of an electrically conducting non-Newtonian power law fluid flowing over a non-linear stretching surface in the presence of a transverse magnetic field taking into consideration viscous dissipation effects is investigated. The stretching velocity, the temperature and the transverse magnetic field are assumed to vary in a power-law with the distance from the origin.
Keywords: magneto-hydrodynamic flow; power-law fluids; stretching sheet; heat source/sink; viscous dissipation